In situ generation of endohedral metallocenophanes of cobalt and rhodium with one cyclopentadienone unit - Scholz, Gerald; Schaefer, Carsten; Rominger, Frank; Gleiter, Rolf (Organic letters, 2002)
Endohedral metallocenophanes of cobalt and rhodium were prepared using thermolysis of cyclopentadienylmetaldicarbonyl complexes bearing two alkyne units. In the case of the rhodium cyclopentadienonophanes, the structures of two isomeric complexes were confirmed by X-ray diffraction analysis.